Central banking and the infrastructural power of finance: the case of ECB support for repo and securitization markets. (20th February 2018) - Braun, Benjamin
Abstract: The pre-crisis rise and post-crisis resilience of European repo and securitization markets represent political victories for the interests of large banks. To explain when and how finance wins, the literature emphasizes lobbying capacity (instrumental power) and the financial sector's central position in the economy (structural power). Increasingly, however, finance also enjoys infrastructural power, which stems from entanglements between specific financial markets and public-sector actors, such as treasuries and central banks, which govern by transacting in those markets. To demonstrate the analytical value of this perspective, the article traces how the European Central Bank (ECB), motivated by monetary policy considerations, has shaped post-crisis financial policymaking in the EU. It shows that the ECB has played a key part in fending off a financial transaction tax on repos and in shoring up and rebuilding the securitization market. With market-based forms of state agency on the rise, infrastructural entanglement and power shed new light on the politics of finance.